2003
DOI: 10.1093/intimm/dxg025
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronous differentiation models explain bone marrow labeling kinetics and predict reflux between the pre- and immature B cell pools

Abstract: B lymphopoiesis has historically been depicted as a unidirectional process, in which cohorts of developing cells transit through successive differentiative stages in an irreversible, synchronous manner. Here, we examine this view by combining kinetic analysis of developing B cell subsets in the bone marrow with mathematical modeling. Our bromo-deoxyuridine (BrdU) labeling data are incompatible with B cell development being a synchronous process, because labeling curves are non-linear. Moreover, we show that B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 57 publications
1
37
0
Order By: Relevance
“…In a more recent study, Tze et al (16) reported that interruption of basal signaling through the BCR results in apparent reversion of affected B cells to an earlier developmental stage and secondary L chain rearrangement. Reversion of immature B cells to an earlier stage during the course of normal B cell differentiation was actually suggested earlier by Mehr et al (17) based on mathematical modeling of the kinetics of developing B cell subsets in BM.…”
mentioning
confidence: 70%
“…In a more recent study, Tze et al (16) reported that interruption of basal signaling through the BCR results in apparent reversion of affected B cells to an earlier developmental stage and secondary L chain rearrangement. Reversion of immature B cells to an earlier stage during the course of normal B cell differentiation was actually suggested earlier by Mehr et al (17) based on mathematical modeling of the kinetics of developing B cell subsets in BM.…”
mentioning
confidence: 70%
“…Although the pre-BCR can engender some skewing of V gene usage (13), specificity-mediated selection commences during the immature and transitional stages, inasmuch as these are where a complete Ag receptor is first expressed. Furthermore, although alternative or branched routes may exist (14,15), and strategies used to subdivide transitional stages vary (11,12), this is likely the major route of maturation for primary B cells. Evidence for stringent selection at this juncture was first suggested by analyses of production and turnover rates in bone marrow vs peripheral populations (9, 10, 16 -19).…”
Section: Both Negative and Positive Selection Occur Among Transitionamentioning
confidence: 99%
“…In addition, defects in hematopoietic stem cells (HSCs) that influence B lymphopoiesis have been described in aging. These include defects in telomere maintenance [18-20]; epigenetic modifications [21]; skewing of lineage potential from lymphopoiesis towards myelopoiesis [22-24]; altered development in the BM [25] and failure to generate a naïve young-like B cell repertoire [26]. …”
Section: Introductionmentioning
confidence: 99%
“…Mathematical models have been used to extract parameters from labeling experiments for better interpretations of the results, which otherwise are very often misinterpreted. For example, we have used the combination of BrdU labeling and mathematical models to study the development and maturation of T cells [44, 45], B cells [25, 46] and NK cells (Elemans et al, manuscript in preparation). These studies led to the discoveries of feedbacks in T cell development [47], blind homeostasis in peripheral T cell populations [48], and phenotypic reflux in B cell development [25].…”
Section: Introductionmentioning
confidence: 99%